2020
DOI: 10.3390/antibiotics9010015
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Diversity, Biofilm Formation, and Antimicrobial Resistance among Stenotrophomonas maltophilia Strains from Cystic Fibrosis and Non-Cystic Fibrosis Patients

Abstract: The intrinsic antibiotic resistance of Stenotrophomonas maltophilia, along with its ability to form biofilm both on abiotic surfaces and host tissues, dramatically affects the efficacy of the antibiotic therapy. In this work, 85 S. maltophilia strains isolated in several hospital of central Italy and from several clinical settings were evaluated for their genetic relatedness (by pulsed-field gel electrophoresis, PFGE), biofilm formation (by microtiter plate assay), and planktonic antibiotic resistance (by Kirb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
3
39
0
3
Order By: Relevance
“…Interestingly, the same concentration of PYED-1 has a synergistic effect with gentamicin or amikacin on bacterial growth inhibition. This is in agreement with other studies showing that S. maltophilia biofilm formation plays a notable role in the development of antibiotic resistance [20][21][22].…”
Section: Effects Of Pyed-1 On the Formation Of S Maltophilia Biofilmsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, the same concentration of PYED-1 has a synergistic effect with gentamicin or amikacin on bacterial growth inhibition. This is in agreement with other studies showing that S. maltophilia biofilm formation plays a notable role in the development of antibiotic resistance [20][21][22].…”
Section: Effects Of Pyed-1 On the Formation Of S Maltophilia Biofilmsupporting
confidence: 93%
“…Most S. maltophilia strains form biofilms on several biotic and abiotic surfaces, and this greatly contributes to the pathogenicity of these bacteria [20][21][22]. Thus, the antibiofilm properties of PYED-1 against S. maltophilia K279a were investigated.…”
Section: Effects Of Pyed-1 On the Formation Of S Maltophilia Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…Mowat et al ( 2007 ) showed that amphotericin B, itraconazole, voriconazole, and caspofungin were 1,000 times less efficient on biofilm-life form than on planktonic form. Several studies showed that levofloxacin could be an alternative to treat S. maltophilia infections (King et al, 2010 ; Wu et al, 2013 ; Herrera-Heredia et al, 2017 ; Pompilio et al, 2020 ). This molecule could reduce biofilm biomass (Di Bonaventura et al, 2004 ; Passerini de Rossi et al, 2009 ), but some levofloxacin-resistant strains emerge (Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of S. maltophilia infection can exceed 35% [ 3 ], with the World Health Organization (WHO) listing S. maltophilia as one of the leading multidrug-resistant pathogens [ 4 ]. The most known S. maltophilia features contributing to its successful adaptation in clinical environments include intrinsic antibiotic resistance mechanisms and its ability to form biofilms [ 5 ], although other less characterized factors (synthesis of extracellular enzymes, bacterial motility, and quorum sensing) are also known to influence its pathogenesis [ 6 ]. S. maltophilia is also known as a highly diverse species, since numerous studies have revealed genotypic diversity between clinical S. maltophilia isolates [ 7 , 8 , 9 ], even when analyzing samples from the same hospital [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%